Peak Loads and Efficient Pricing: Reply - Steiner, Peter O. (Quarterly Journal of Economics, 1958)
Journal Article Peak Loads and Efficient Pricing: Reply Get access Peter O. Steiner Peter O. Steiner University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 72, Issue 3, August 1958, Pages 465–468, https://doi.org/10.2307/1882236 Published: 01 August 1958